A 'new spirit' of public policy? The project world of EU funding. Issue 1 (2nd January 2016) - Büttner, Sebastian M.; Leopold, Lucia M.
ABSTRACT: Starting from the assumption that projects have become an important form of social organisation in contemporary working life, we examine the proliferation of 'projects' in public policy, especially in European Union (EU) policy-making. Project logic constitutes an influential element of policy implementation in Europe; and it substantially influences the way EU policies are implemented all over the EU territory and beyond. Drawing on sociological takes on public policy instrumentation, we discuss the emergence, the establishment and major cultural logics of project-based policy funding. We show that EU funding constitutes an own field of expertise, a distinct 'project world', so to speak, with specific standards, regulations, practical conventions and a particular rhetoric. This brings about an increasing expertisation of EU policy-making and certain exclusionary effects, despite all efforts to bring the Union closer to the citizens' through project funding.